Sedentary Screen Time as a Coping Strategy of Distance Learning-induced Distress during COVID-19 Pandemic - Ghea Mangkuliguna; Mahaputra Mahaputra; Veronika Maria Sidharta; Linawati Hananta (Universitas Ahmad Dahlan, 2021)
During the COVID-19 pandemic, medical students might be vulnerable to excessive screen time exposure to cope with distance learning-induced distress. This study aimed to evaluate the distress and screen time before and after distance learning was initiated. Data were collected from 215 subjects. Statistical significance was accepted at P<0.05. The prevalence of distress among medical students was 25.61% and 27.06% before and after distance learning was executed, respectively. Academic-related stressor (ARS) was reported by 49.28% and 63.29% of students during the first and second surveys. The proportion of students with daily screen time ≥7 hours was 51.21% and 63.77% for the first and second surveys, respectively. ARS, interpersonal and intrapersonal-related stressor (IRS), social-related stressor (SRS), and average daily screen time significantly rose in 3-month-time (P<0.0001, P=0.0014, P=0.0261, P=0.0022). There was a significant association between distress and screen time (P=0.0313). ARS was the leading cause of distress. The majority of respondents had a daily screen time ≥7 hours. Both distress and screen time levels significantly increased as distance learning kept progressing.Keywords: COVID-19; distance learning; mental distress; medical students; screen time.